The Impact of Employee Satisfaction on Customer Service Quality in Islamic Bank - Alfalisyado, Alfalisyado (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2020)
The aim of this study is to examine the impact of employee satisfaction on customer service quality. The subject of this research is Islamic banks in Indonesia with two variables are employee satisfaction and customer service quality. The results of this study is shown that there is a relationship between employee satisfaction and customer service quality. The degree of influence of employee satisfaction to customer service quality is 13.1% which mean there are many variables can be determined for the next research.